Pengaruh Struktur Modal, Perputaran Modal Kerja, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Muhammad Rhamadan Setiawan; Neneng Susanti; Nugi Mohammad Nugraha (Politeknik Ganesha Medan, 2021)
This study aims to obtain empirical evidence regarding the effect of capital structure, working capital turnover, and firm size on firm value. This research is focused on the property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. The population in this study were all property and real estate sub-sector companies listed on the Indonesia Stock Exchange as many as 54 companies. The number of observations in this study was as many as 130 company annual reports with 26 research samples obtained by non-probability sampling method, namely purposive sampling technique. The type of data used is panel data which is a combination of time series and cross-section data. The analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that partially the three independent variables, namely capital structure, working capital turnover, and company size have a significant effect on firm value. Simultaneously, Capital Structure, Working Capital Turnover, and Company Size have a significant effect on Firm Value. The adjusted R square value is 32.15% of the Firm Value in the property and real estate sub-sector companies listed on the Indonesia Stock Exchange can be explained by the Capital Structure, Working Capital Turnover, and Company Size, while the remaining 67.85% is influenced by other variables. which were not examined in this study